Protein Self‐Assembly: A Superhydrophobic Surface Templated by Protein Self‐Assembly and Emerging Application toward Protein Crystallization (Adv. Mater. 3/2016). Issue 3 (14th January 2016) - Gao, Aiting; Wu, Qian; Wang, Dehui; Ha, Yuan; Chen, Zhijun; Yang, Peng
Abstract : On page 579, by rationally manipulating the lysozyme phase transition, P. Yang and co‐workers report the first proteinaceous superhydrophobic material for facile protein crystallization. A reliable protein‐based superhydrophobic coating on virtually arbitrary material surfaces is achieved with good thermostability and mechanical robustness. Such a surface exhibits a fascinating capability to drive protein crystallization.